PKM STRENGTHENING CHARACTER THROUGH ISLAMIC COMPETITIONS FOR ELEMENTARY SCHOOL STUDENTS IN GOWA REGENCY - Muhammad Radhi Almardhi; Sitti Muthmainnah; Tauhidah Bachtiar; Fauziah Bachtiar (PT. Jurnal Center Indonesia Publisher, 2025)
This Community Partnership Program (PKM) aims to strengthen the character of elementary school students through Islamic competitions. The background of this activity is the importance of character education at the elementary school level, which is a crucial phase in shaping children’s personalities. The implementation method employed a participatory approach by involving students, teachers, and parents in various Islamic competitions, such as the call to prayer (adhan), Qur’anic speech (syarhil Qur’an), Qur’anic recitation (tartil) and memorization (hifdzul Qur’an), calligraphy decoration, and Islamic quiz competitions. These activities were designed not only as competitive events but also as educational media for the internalization of Islamic values such as discipline, responsibility, honesty, cooperation, and self-confidence. The results indicated an increase in students’ motivation to learn religion, discipline in worship, and the development of mutual respect among peers. Therefore, Islamic competitions proved to be effective in strengthening the character of elementary school students while serving as an alternative community service activity that benefits both schools and society.